The effects of uncertainty on investor expectations and volatility in the South African white maize futures market. Issue 3 (2nd July 2020) - Auret, Christo; Sayed, Ayesha
ABSTRACT: Given the rapidly changing nature of financial markets, volatility indices often influence the trading behaviour of market participants, as they identify market patterns, predict market risk and gauge market sentiment. This paper examines the effects of uncertainty on the expectations of South African white maize futures traders and on volatility at a daily level. Uncertainty effects are measured using three volatility indices: The SAVI Top 40, the SAVI Dollar and the SAVI White Maize. Investor expectations in the South African white maize futures market are proxied by three momentum indicators, the moving average convergence divergence (MACD), the relative strength index (RSI) and the rate of change (ROC). Volatility is estimated using a fitted GARCH (1, 1) model of South African white maize futures closing prices. A time-varying vector autoregressive (VAR) framework is used to examine the reactions of each of the three momentum indicators to shocks from each of the three volatility indices. The results confirm that changes in uncertainty influence the expectations of South African white maize futures momentum traders; and that these resulting trades influence price movements, resulting in increased volatility.